Judiciary Problems in Mature Democratic Countries: American and French Perspectives - Kwasau, Muhammad Aminu; Maina, Salma Abdurrahman; Shafiu, Raziqa Muhammad; Shafiu, Mariyah Muhammad (Faculty of Law, Universitas Sebelas Maret, 2023)
Even when all other safeguards fail, a judiciary of unquestionable integrity is the cornerstone institution necessary for guaranteeing adherence to democracy and the rule of law. It protects the public from any violations of their legal rights and freedoms.This observation applies to both global analyses of the judicial system and rule of law process in America and France, in particular. The judiciary and legal adjudication process were viewed and examined as a great bastion of the rule of law throughout the United States of America and France as one of the great countries that are characterized as mature democracies in this paper, which relied on the qualitative method of data collection. The study discovered that, in contrast to France, which has a centralized legal system, the United States has two distinct judicial systems (federal and state).